Production and distribution in political-economic systems: A non-atomic game - Alex Coram (University of Massachusetts, Department of Economics, 2017)
Societies are often compared in terms of the relative shares of the domestic product controlled by government but we don't have much by way of analytical tools to allow us to think about the ways in which changes in these shares affect the characteristics of production and distribution. This paper treats production and distribution as a cooperative game with a continuum of players. Outcomes depend on politics and economics. It has a number of unexpected results. Among these are that relative shares do not depend on the majority rule the production function and that the characteristics of inegalitarian and egalitarian systems may converge.
Keywords: 330